Analisa dan Pemetaan Kepadatan Hutan Mangrove di Wilayah Pesisir Pantai Gresik - Miftahul Ulum Wilianto; Siti Zainab (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The mangrove forest ecosystem in Ujung Pangkah sub-district plays a very important role in the lives of living creatures around it. The management and use of mangrove ecosystems by people in this sub-district tends to lead to the conversion of land into ponds, whether in the form of forest or emerging land. Cutting down trees in mangrove gforests is one of the causes of abrasion in several areas in Indonesia. Apart from abrasion, there is also accretion or addition of land around the Bengawan Solo estuary which provides access to the Pangkahwetan and Pangkahkulon coasts. The aim is to analyzezchanges in the area of mangrove vegetationgin Ujungpangkah. This research uses a remote sensing method known as the resolution concept, namely spatial resolution, temporal resolution, spectral resolution, radiometric resolution and layer resolution. Quantitative observations were made of changes in mangrove forest area using Landsat -8 imagery. The location of the Ujungpangkah ground is based on the conditions of the study location, in accordance with the results of initial image processing. Changes in the area of mangrove vegetation when viewed from remote sensing results in 2023 and 2024 experience visible differences, the distribution of mangroves will increase in 2024, namely there will be an increase in the area of vegetation. The distribution area of mangroves always changes every year. Either in the form of addition or reduction of area. Things that can affect the extent of mangrove distribution include 2 types of damage to the mangrove ecosystem in Ujung Pangkah District, namely abrasion and deforestation. The efforts made to overcome this problem include starting mangrove planting activities in the Banyuurip Mangrove Center (BMC) area. The results of data processing from the 2023 RBI map in Ujungpangkah District recorded a total area of ​​11904.93052 ha. The area is divided into several land uses, namely Mangrove covering an area of ​​1253.24609 ha and Non-Mangrove covering an area of ​​1525.32660 ha. Meanwhile, processing data from Lansat-8 in 2024 in Ujungpangkah District, the total area was recorded at 11904.93052 ha. Mangrove land use was recorded at 10651.68443 ha and non-mangrove land at 10379.60392 ha.